Transformation and development of the Islamic Capital Market in the Digitalization Era : Bahasa Indonesia - Evelyn Halilah Faiqoh (ITB AAS INDONESIA Surakarta, 2025)
The Islamic capital market in Indonesia has experienced significant development since its official establishment in 2003. Digital transformation has been a key factor in driving this market's growth by expanding investor access and improving transaction efficiency and transparency. This study employed a qualitative approach with a literature review method that analyzed various secondary sources, such as scientific journals, Financial Services Authority (OJK) regulations, fatwas from the National Sharia Council (DSN-MUI), and official documents related to the Islamic capital market. The results show that digitalization has significantly contributed to strengthening financial inclusion and Sharia-based supervision of Islamic stocks, sukuk, and mutual funds. Despite challenges such as low financial literacy and the need for regulatory standardization, digitalization opens up opportunities for inclusive and sustainable growth in the Islamic capital market. This study proposes strategic recommendations to strengthen synergy between the government, regulators, and market players in building a Sharia capital market ecosystem in the digital era.